A fluorescence probe for bisulfite sensing based on the bisulfite-induced binding site transfer between Zn2+ and an aminoquinoline derivate. (December 2018) - Wei, Tingwen; Wang, Fang; Chen, Yahui; Qiang, Jian; Zhang, Zhijie; Chen, Tiantian; Chen, Xiaoqiang
Abstract: A fluorescent probe is constructed to quickly and accurately detect bisulfite. The detection mechanism was considered to operate via the bisulfite, causing deprotonation of amido bond of 8-aminoquinoline derivative leading to fluorescence enhancement. The probe has a good selectivity for bisulfite over the other competitive substances such as F −, Cl −, Br −, I −, C2 O4 2−, NO2 −, ClO4 −, OAc −, PO4 3−, CO3 2−, HCO3 −, HS −, HSO4 −, SCN −, SO4 2−, S2 O3 2−, Cys, Hcy and GSH. There is a good linear relationship between fluorescence intensity and the concentration of bisulfite in the range of 0–200 μM. The limit of detection was calculated to be 0.61 μM. Furthermore, the probe has also been successfully used for imaging bisulfite in living cells. Graphical abstract: Image 1 Highlights: In this paper, a new strategy for the detection of bisulfite is proposed. The probe exhibited good selectivity to bisulfite among various anions and biothiols. The high sensitivity of the probe with detection limit of 0.61 μM were determined. The probe can be used for imaging bisulfite in living Hela cells.